Dichorionic twins and monochorionic triplets after the transfer of two blastocysts - Ferreira, Marcelo (Springer US, 2010)
PURPOSE: To describe a unique case of MZ dichorionic twins and MZ monochorionic triplets in a quintuplet gestation after intracytoplasmatic sperm injection (ICSI) and blastocyst transfer. METHODS: Case report. A 24-year-old woman underwent ICSI and received two blastocysts transferred. A quintuplet gestation was established .Transvaginal ultrasonography was performed sequentially during early pregnancy. RESULTS: Three intrauterine gestational sacs were revealed at about 5th week. At the 7th week, five gestational sacs presenting heart beats were detected and a quintuplet pregnancy consisting of two monozygotic (MZ) dichorionic twins and three MZ monochorionic triplets was determined. At the 10th week, a single gestational sac with heart beats was detected. The prenatal course was uneventful. A healthy baby was born at 36th week. CONCLUSION: Few other reports have described the occurrence of a quintuplet gestation after the transfer of two blastocysts generated by ICSI. Our case is unique in that the two blastocysts underwent two different splitting processes, which occurred possibly at a similar time giving rise to MZ dichorionic twins and MZ monochorionic triplets.